Periodontitis aggravates kidney injury by upregulating STAT1 expression in a mouse model of hypertension - Qin Yang; Handong Ding; Wei Wei; Jie Liu; Jiajia Wang; Jie Ren; Weicheng Chan; Min Wang; Liang Hao; Jinle Li; Yuan Yue (FEBS Open Bio, 2021)
Periodontitis is an autoimmune disease of periodontal tissues initiated by plaque. It is known that there is a close connection between periodontitis and CKD with hypertension, but the underlying mechanisms are unknown. STAT1 has been reported to play a regulatory role in hypertension and chronic kidney disease (CKD). Here, we investigated whether STAT1 regulates periodontitis‐mediated aggravation of kidney injury with accompanying hypertension. A hypertensive renal injury mouse model was established with Nos3 knockout mice, and a periodontitis model was established by implantation with the oral bacteria Porphyromonas gingivalis. The mice were intraperitoneally injected with a STAT1 inhibitor. Periodontitis aggravated kidney injury in hypertensive mice, and upregulation of STAT1 was observed when both periodontitis and hypertension were present; furthermore, STAT1 inhibitor moderated this effect. Moreover, we observed that periodontitis promoted the upregulation of inflammatory and fibrosis gene expression in the kidneys of hypertensive mice. In addition, STAT1 inhibition decreased the expression of pro‐inflammatory and pro‐fibrotic cytokines in the kidney lesion area. Periodontitis augmented the expression of inflammatory and fibrosis genes by upregulating the expression of STAT1, thereby aggravating kidney injury in the hypertensive mouse model.